2022
DOI: 10.1038/s41591-022-02078-6
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen alleles associate with COVID-19 vaccine immunogenicity and risk of breakthrough infection

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine immunogenicity varies between individuals, and immune responses correlate with vaccine efficacy. Using data from 1,076 participants enrolled in ChAdOx1 nCov-19 vaccine efficacy trials in the United Kingdom, we found that inter-individual variation in normalized antibody responses against SARS-CoV-2 spike and its receptor-binding domain (RBD) at 28 days after first vaccination shows genome-wide significant association with major histocompatibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 51 publications
3
53
3
Order By: Relevance
“…Importantly, however, it appears that RBD-specific CD4 T cells could be boosted to some extent by vaccination. A very recently published study of vaccination shows an association between carriage of the HLA-DQB1*06 allele and combined higher antibody and CD4 T cell proliferation responses to RBD, following vaccination, which was postulated to be due to improved presentation of an epitope adjacent to the RBD ( 87 ). Our results suggest that booster efficacy would be improved by concentrating on CD4 T cell epitopes in and around the RBD, which may be the optimal regimen for generation and longevity of neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, however, it appears that RBD-specific CD4 T cells could be boosted to some extent by vaccination. A very recently published study of vaccination shows an association between carriage of the HLA-DQB1*06 allele and combined higher antibody and CD4 T cell proliferation responses to RBD, following vaccination, which was postulated to be due to improved presentation of an epitope adjacent to the RBD ( 87 ). Our results suggest that booster efficacy would be improved by concentrating on CD4 T cell epitopes in and around the RBD, which may be the optimal regimen for generation and longevity of neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the HLA DQB1*06 allele also appeared to confer some protection against breakthrough SARS-CoV-2 infection as shown by the observation that HLA-DQB1*06 was present in 45.6% of individuals who did not have breakthrough infection compared with presence of that allele in 33.9% of individuals who experienced breakthrough infection [2]. This difference in prevalence of HLA-DQB1*06 was significant at the level of p = 0.02.…”
Section: Regarding: Factors Associated With Severe or Fatal Clinical ...mentioning
confidence: 92%
“…Dear Editor, Among the wide range of variables which are associated with severe or fatal clinical manifestations of SARS-CoV-2 infection after receiving the third dose of vaccine [1], one also ought to include human leukocyte antigen (HLA) allele status [2]. The rationale is that HLA status significantly influences SARS-CoV-2 vaccine immunogenicity as well as liability to develop breakthrough infection attributable either to the ancestral SAR-CoV-2 infection or the alpha variant [2]. In the latter study, the authors analysed data from 1076 participants enrolled in ChAdOx1nCov-19 vaccine efficacy trials in the United Kingdom.…”
Section: Regarding: Factors Associated With Severe or Fatal Clinical ...mentioning
confidence: 99%
“…In a recent study, Naranbhai and colleagues showed that spike mutations in Omicron could escape T-cell responses in an HLA-dependent manner (12). Notably, a research group at the Oxford University recently reported an association of HLA alleles, specifically the HLA-DQB1*06 alleles with higher antibody response following immunization against the SARS-COV-2 vaccine and with a lower risk of breakthrough SARS-COV-2 infection (13).…”
Section: What Are the Underlying Pathophysiological Mechanisms Of Lon...mentioning
confidence: 99%